Wittgenstein’s Methodology of Gestalt Psychology - Ter Hark, Michel (JoLMA)
This article proposes a methodological understanding of Wittgenstein’s remarks about Gestaltpsychology. Wittgenstein is not so much concerned with Gestaltpsychology proper but rather with its understanding of the nature of the problem of seeing (and seeing-as) as dealt with by British empiricism. Gestaltpsychology offers a more sophisticated physiological explanation of seeing and seeing-as than empiricism has done, yet also this explanation bypasses the (conceptual) problem. Physiological explanations are not eschewed by Wittgenstein, he even gives himself interesting physiological hypotheses. The problem with physiological explanations is that they focus on particular items in the brain as underpinning our use of concepts like seeing and seeing as, whereas they are constituted by our reactions and responses to what we see. Such reactions are embedded in language games and acquire their meaning by our ‘forms of life’ rather than the human brain. This interpretation is finally applied to Wittgenstein’s and Köhler’s explanation of social understanding